The Effects of 10 Weeks Hangboard Training on Climbing Specific Maximal Strength, Explosive Strength, and Finger Endurance - Hermans, Espen; Saeterbakken, Atle H.; Vereide, Vegard; Nord, Ivar S. O.; Stien, Nicolay; Andersen, Vidar (Frontiers in Sports and Active Living, 2022)
The aim of this study was to investigate the effects of 10 weeks hangboard training on climbing specific maximal strength, explosive strength, and muscular endurance. Thirty-five intermediate- to advanced level climbers (8 females, 27 males) were randomized into a hangboard training group (HBT) or a control group (CON). The hangboard training program consisted of two sessions of 48 minutes per week using the Beastmaker 1000 series hangboard, and the following application to smart phone. Both groups continued their normal climbing training routines. Pre- and post-intervention, maximal peak force, maximal average force and rate of force development (RFD) were measured while performing an isometric pull-up on a 23mm deep campus rung and jug holds. In addition, finger endurance was measured performing a sustained dead-hang test on the same rung. The HBT increased peak force and average force in 23mm rung condition, average force in jug condition and utilization rate in peak force to a greater extent than CON (p = 0.001 – 0.031, ES = 0.29 – 0.66), whereas no differences were detected between groups in RFD (jug or 23mm), peak force in jug condition, utilization rate in RFD and average force, or in dead-hang duration (p = 0.056 - 0.303). At post-test, the HBT group demonstrated 17%, 18%, 28%, 10%, 11% and 12% improvement in peak force, average force, RFD in 23mm rung condition, average force in jug condition, utilization rate in peak force and dead-hang duration, respectively (p = 0.001 – 0.006, ES = 0.73 - 1.12) whereas no change was observed in CON (p = 0.213 – 0.396). In conclusion, 10 weeks of hangboard training in addition to regular climbing was highly effective for increasing maximal finger strength compared to continuing regular climbing training for intermediate and advanced climbers.